Interventions for developmental delays in children born to HIV-infected mothers: a systematic review. Issue 3 (4th March 2019) - McHenry, Megan Song; McAteer, Carole Ian; Oyungu, Eren; Deathe, Andrew Roland; Vreeman, Rachel Christine
ABSTRACT: Children born to HIV-infected mothers have worse developmental outcomes compared to HIV-unexposed children. However, little is known about interventions to improve developmental outcomes in this population. This study systematically reviews the literature on interventions to improve development in children born to HIV-infected mothers. We systematically searched the following electronic bibliographic databases: Ovid MEDLINE, Embase, PsycINFO, Education Resources Information Center, and the Cochrane Database of Systematic Reviews. Studies were selected on the basis of defined inclusion criteria and excluded if antiretroviral medication was the only intervention. Titles, abstracts, and full texts were assessed by 2 independent reviewers. Data were collected on characteristics of the study design, intervention, and developmental outcomes measured. Risk of bias and strength of evidence were assessed on all included articles. Our search resulted in 11, 218 records. After our initial review, 43 records were appraised in their entirety and 9 studies met all inclusion criteria. Six were performed in sub-Saharan Africa, while the remaining 3 were performed in the United States. Eight were randomized-controlled trials and one was a retrospective chart review. Four studies focused on caregiver-training, 2 studied massage therapy, and the remaining studies focused on maternal vitamin supplementation, video-based cognitive therapy, or center-based interventions. Massage therapy had the most consistent improvements in the domains measured, while caregiver training and cognitive therapy interventions had limited benefits. The center-based intervention showed no benefit. Only 3 studies had a low risk of bias, and 4 studies had good strength of evidence. Most studies found some benefit. However, these findings are limited by the quality of the study designs, small sample size, and heterogeneity of the interventions and assessments used to measure outcomes. There is a critical need for the creation of evidence-based interventions to promote development in this vulnerable population.